2017
DOI: 10.1007/s10147-017-1182-2
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 gene: function and deficiency

Abstract: The BRCA1 protein, a hereditary breast and ovarian cancer-causing gene product, is known as a multifunctional protein that performs various functions in cells. It is well known, along with BRCA 2, to cause hereditary breast and ovarian cancer, but here we will specifically focus on BRCA1. We introduce the mechanism and the latest report on homologous recombination repair, replication, involvement in checkpoint regulation, transcription, chromatin remodeling, and cytoplasmic function (centrosome regulation, apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
70
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 90 publications
0
70
0
6
Order By: Relevance
“…In the case of serous ovarian cancers, up to 25% of cases contain germline mutations with the most common being BRCA1 or BRCA2 mutations [2]. BRCA1/2 are multi-functioning tumor suppressor proteins that play a vital role in homologous recombination repair (HRR) of double-stranded DNA breaks (DSBs), cell cycle checkpoint activation, replication fork (RF) protection, and generating single-stranded DNA during repair after irradiation damage [3][4][5]. Defective HRR predisposes cancer cells to increased genomic instability and represents a unique vulnerability that can be exploited by anticancer therapy directed at complementary pathways.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of serous ovarian cancers, up to 25% of cases contain germline mutations with the most common being BRCA1 or BRCA2 mutations [2]. BRCA1/2 are multi-functioning tumor suppressor proteins that play a vital role in homologous recombination repair (HRR) of double-stranded DNA breaks (DSBs), cell cycle checkpoint activation, replication fork (RF) protection, and generating single-stranded DNA during repair after irradiation damage [3][4][5]. Defective HRR predisposes cancer cells to increased genomic instability and represents a unique vulnerability that can be exploited by anticancer therapy directed at complementary pathways.…”
Section: Introductionmentioning
confidence: 99%
“…7 It includes cell cycle control, DNA repair, transcription and ubiquitination. 8,9 BRCA1 suppresses tumor growth in a PCa experimental model. 10 BRCA1-mutated or -deficient breast cancer cells seem to have more invasive phenotype including higher proliferation rate 11 and migration abilities.…”
Section: Introductionmentioning
confidence: 99%
“…Although the 5′UTR‐20 G/A SNP was not associated with T2DM, the analysis in silico showed that the A allele produces a binding motif for the BRCA1 transcription factor. The BRCA1 tumor suppressor is a protein that has an important role in multiple biochemical and biological functions such as DNA repair, replication, cell cycle checkpoints, protein ubiquitination, transcriptional regulation, chromatin remodeling, and apoptosis (Takoaka & Miki, ). Recently, Kang et al () reported that BRCA1 regulates the expression of insulin‐like growth factor receptor‐1 (IGF‐IR) in human breast cancer cell line (MCF7).…”
Section: Discussionmentioning
confidence: 99%